Investigation of a public hospital cluster of COVID-19 cases in Bangkok - Chotigadachanarong, Pleumjai; Osothsinlp, Sornwit; Prasan, Shewarat; Chongchitpaisan, Wanna (Disease Control Journal, 2023)
A cluster of 17 COVID-19 cases in the female surgical ward was reported to the outbreak investigation team of a public hospital in Bangkok. After the first confirmed case was detected on September 2, 2021, an outbreak investigation was conducted during September 2-10, 2021 in order to confirm the outbreak and diagnosis of COVID-19, study epidemiological characteristics, and implement appropriate outbreak control measures. Descriptive epidemiological study was conducted by chart review, interviewing healthcare workers, evaluating the environmental factors of the female surgical ward, and taking nasopharyngeal swabs (NP swab) for confirmatory COVID-19 Realtime RT-PCR test. The first confirmed case was a 54-year old female. Based on the outbreak investigation and active case finding, 45 high-risk contacts were identified. Of these 45 high-risk contacts, 21 were patients in the ward and 24 were healthcare workers. A total of 17 confirmed cases of COVID-19 infections were detected – i.e. 15 patients in the ward (31.11%) and 2 nurses (4.45%). The attack rate was 37%. This outbreak was caused by propagated sources. Nevertheless, the source of this outbreak could not be determined. Prior to the outbreak, according to hospital rules, all admitted patients had tested negative by RT-PCR. However, it was found that patients had failed to adhere to the universal masking requirements in a healthcare setting and healthcare workers did not properly use Personal Protective Equipment (PPE). The points of weakness were lack of robust preventive and infection control measures, as well as a limitation of screening tests for patients who may have COVID-19 related illnesses. To prevent future outbreaks, the hospital should therefore improve disease preventative measures to be more effective. Additionally, they should also improve the environments in the wards and emphasize the importance of wearing appropriate PPE to patients, visitors, and healthcare workers. As patients and healthcare workers were considered high-risk groups, they should be encouraged to receive COVID-19 vaccination.